Glyceraldehyde-3-phosphate dehydrogenase acts as a mitochondrial trans-S-nitrosylase in the heart. - Mark J Kohr; Elizabeth Murphy; Charles Steenbergen (PLoS ONE)
Mitochondrial proteins have been shown to be common targets of S-nitrosylation (SNO), but the existence of a mitochondrial source of nitric oxide remains controversial. SNO is a nitric oxide-dependent thiol modification that can regulate protein function. Interestingly, trans-S-nitrosylation represents a potential pathway for the import of SNO into the mitochondria. The glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which has been shown to act as a nuclear trans-S-nitrosylase, has also been shown to enter mitochondria. However, the function of GAPDH in the mitochondria remains unknown. Therefore, we propose the hypothesis that S-nitrosylated GAPDH (SNO-GAPDH) interacts with mitochondrial proteins as a trans-S-nitrosylase. In accordance with this hypothesis, SNO-GAPDH should be detected in mitochondrial fractions, interact with mitochondrial proteins, and increase mitochondrial SNO levels. Our results demonstrate a four-fold increase in GAPDH levels in the mitochondrial fraction of mouse hearts subjected to ischemic preconditioning, which increases SNO-GAPDH levels. Co-immunoprecipitation studies performed in mouse hearts perfused with the S-nitrosylating agent S-nitrosoglutathione (GSNO), suggest that SNO promotes the interaction of GAPDH with mitochondrial protein targets. The addition of purified SNO-GAPDH to isolated mouse heart mitochondria demonstrated the ability of SNO-GAPDH to enter the mitochondrial matrix, and to increase SNO for many mitochondrial proteins. Further, the overexpression of GAPDH in HepG2 cells increased SNO for a number of different mitochondrial proteins, including heat shock protein 60, voltage-dependent anion channel 1, and acetyl-CoA acetyltransferase, thus supporting the role of GAPDH as a potential mitochondrial trans-S-nitrosylase. In further support of this hypothesis, many of the mitochondrial SNO proteins identified with GAPDH overexpression were no longer detected with GAPDH knock-down or mutation. Therefore, our results suggest that SNO-GAPDH can act as a mitochondrial trans-S-nitrosylase, thereby conferring the transfer of SNO from the cytosol to the mitochondria.